KARAKTERISTIK TARI RABBANI WAHED PADA MASYARAKAT ACEH KECAMATAN SAMALANGA KABUPATEN BIREUN - Rika Restella Rika Restela (Universitas Negeri Medan, 2013)
This study discusses the shape and characteristics of the Dance Rabbani Wahed. This form of dance seen from the origin, round, movement, poetry, and fashion in dance. Then to look at the characteristics of the Dance Rabbani Wahed can be seen from the role, nature and character contained in the movement, round, and poetry. Theoretical foundation used in this study is the theory and the theory of characteristic shape. In theory there are characteristics of role theory, the theory of the nature and character of the theory. The method used in this research is descriptive qualitative method, interpreted and formulated between the data with other data so that the data is accurate and thorough. Data collection techniques include library research, observation, interview and documentation. Based on the results of research conducted, it can be seen that the characteristic has three parts, namely the role, nature and character. There is a notch on the role (status): Syech, aneuk syahi and dancers. In addition, there is a function that is to teach monotheism and religion so that people always have fear of Allah SWT. On the nature of the views contained compactness of motion, round and chant poems. Then the character of the dance Rabbani Wahed which human perseverance in surrender to God.